2012
DOI: 10.1007/s11920-012-0316-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Childhood Sexual Abuse: An Updated Review

Abstract: Childhood sexual abuse (CSA) involves multiple complex factors that make the evaluation of therapeutic interventions especially complicated. PTSD prevalence rates of CSA are approximately 37 % -53 %. Several other psychiatric sequelae of CSA exist. CSA appears to disrupt brain and body physiology. One co-located service delivery model reported a 52 % linkage rate of CSA survivors with mental health treatment. This article reviews current literature on the treatment of CSA, including psychosocial interventions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 63 publications
0
21
0
3
Order By: Relevance
“…CSA is an important risk factor for several health problems in childhood and in adult life 1,[9][10] that have a great impact on the physical and mainly psychological health of victims. It is also a substantial burden to the health system (medical consultations and hospitalizations) 1,[10][11][12][13][14][15][16][17][18] .…”
Section: O Pai Foi O Maior Responsavel Por Esses Abusosmentioning
confidence: 99%
“…CSA is an important risk factor for several health problems in childhood and in adult life 1,[9][10] that have a great impact on the physical and mainly psychological health of victims. It is also a substantial burden to the health system (medical consultations and hospitalizations) 1,[10][11][12][13][14][15][16][17][18] .…”
Section: O Pai Foi O Maior Responsavel Por Esses Abusosmentioning
confidence: 99%
“…Second, although there are effective treatments for the effects of CSA (Cummings et al 2012), CSA exposure often has complex, long-term negative effects even for those who receive treatment. CSA is associated with emotional and behavioral problems, as well as factors such as substance abuse that increase risk for mental and physical illnesses over the life course (Chen et al 2010;Devries et al 2014;Lindert et al 2014).…”
mentioning
confidence: 99%
“…Notably, cognitive behavioral therapy (CBT) has proven effective in the treatment of childhood PTSD. 54 Recent systematic reviews reported by the Cochrane Collaborative, 55 Silverman et al, 56 Dorsey et al, 57 and a federally funded evidence synthesis on interventions for nonrelational trauma 58 Other CBT trials focusing on physically abused youth demonstrated significant improvements. 64,65 The TFCBT modality incorporates individual CBT and family therapy to reduce not only trauma symptoms but also the use of physical punishment and coercion.…”
Section: Evidence-based Treatment Of Childhood Trauma Overviewmentioning
confidence: 99%